THE DIFFERENCE IN KINEMATIC CHAIN BEHAVIOR BETWEEN PRONATION / SUPINATION OF CALCANEUS AND ROTATION OF SHANK IN STANDING POSITION BY INDIVIDUAL, AGE, GENDER AND RIGHT AND LEFT: ANALYSIS OF KINEMATIC USING OPTICAL THREE DIMENSIONAL MOTION ANALYSIS SYSTEM (International Journal of Physiotherapy, 2018)
Background: Although the kinematic coupling of calcaneus and shank is important for optimizing the pathological movement of the lower extremity, it is not sufficiently clarified. The objective of this study was to represent the kinematic coupling behavior of calcaneal pronation/supination and shank rotation quantitatively while standing and to identify the extent of the individual, age, gender and laterality differences in these measurements.Methods: This study was a cross-sectional study that subjects were 25 healthy young people (17 men and eight women) and 29 healthy elderly people (15 men and 14 women). Kinematic coupling behavior was quantified as the linear regression coefficient (kinetic chain ratio: KCR) of the angle of shank rotation against the angle of calcaneal pronation-to-supination measured using a 3D motion analysis system during pronation and supination of both feet while standing. Individual differences in the KCR, which is an outcome, were also investigated with regard to differences in age, gender, and laterality.Results: The mean KCR in all subjects was 1.00 ± 0.23. In addition, the coefficient of variation (CV) was 22.9%, with individual results varying from a maximum of 1.6 to a minimum of 0.4. The KCR was also larger in men than in women (p